Strategi Bersaing Lembaga Keuangan Syariah dalam Menghadapi Persaingan Industri Keuangan di Jawa Tengah - Miswan Ansori; Faiqul Hazmi (Wahana Islamika: Jurnal Studi Keislaman, 2020)
Along with the development of financial institutions today, the number of Islamic financial institutions is increasing, Indonesia which is one of the countries with the largest majority of Muslim population in the world has the opportunity to further advance Sharia-based financial institutions. In the face of the times and technological developments, Islamic financial institutions must always innovate so that they are no less competitive with conventional financial institutions. If Islamic Financial Institutions do not innovate and make a better difference, Islamic financial institutions will be eroded by time. This study will examine the competitive strategy undertaken by Islamic Financial Institutions in facing competition in the financial industry in Central Java. The research method used is descriptive qualitative by conducting a SWOT analysis so that the strengths, weaknesses of opportunities and threats that exist in Islamic Financial Institutions will be known. This research was conducted by taking data at Bank Syariah Mandiri Semarang, BPRS Saka Dana Mulia Kudus and Kospin Jasa Syariah Jepara.